2010
DOI: 10.1073/pnas.0913016107
|View full text |Cite
|
Sign up to set email alerts
|

Coherent amygdalocortical theta promotes fear memory consolidation during paradoxical sleep

Abstract: Brain activity in sleep plays a crucial role in memory consolidation, an offline process that determines the long-term strength of memory traces. Consolidation efficacy differs across individuals, but the brain activity dynamics underlying these differences remain unknown. Here, we studied how interindividual variability in fear memory consolidation relates to neural activity in brain structures that participate in Pavlovian fear learning. From the end of training to testing 24 h later, some rats showed increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
250
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(281 citation statements)
references
References 51 publications
28
250
0
3
Order By: Relevance
“…Other reward-related regions, like the ventromedial PFC (Haber and Knutson 2010) and the ACC, which assign a positive or negative value to future outcomes (Bush et al 2002;Takenouchi et al 1999), are activated during REM sleep, in both animals and humans (Lena et al 2005;Maquet et al 1996Maquet et al , 2000. In addition, neuronal activity in the hippocampus displays a theta rhythm (i.e., an oscillatory pattern in EEG with a frequency range of 5-12 Hz in behaving rats and 4-7 Hz in humans) during REM sleep in both animals (Popa et al 2010;Winson 1972) and humans (Cantero et al 2003) studies. This latter finding is remarkable considering that increased theta oscillations have been reported during novelty-seeking, exploratory and instinctual behaviors, which are also seen in REM sleep behavior disorder and other parasomnias .…”
Section: Activation Of Reward Networkmentioning
confidence: 99%
“…Other reward-related regions, like the ventromedial PFC (Haber and Knutson 2010) and the ACC, which assign a positive or negative value to future outcomes (Bush et al 2002;Takenouchi et al 1999), are activated during REM sleep, in both animals and humans (Lena et al 2005;Maquet et al 1996Maquet et al , 2000. In addition, neuronal activity in the hippocampus displays a theta rhythm (i.e., an oscillatory pattern in EEG with a frequency range of 5-12 Hz in behaving rats and 4-7 Hz in humans) during REM sleep in both animals (Popa et al 2010;Winson 1972) and humans (Cantero et al 2003) studies. This latter finding is remarkable considering that increased theta oscillations have been reported during novelty-seeking, exploratory and instinctual behaviors, which are also seen in REM sleep behavior disorder and other parasomnias .…”
Section: Activation Of Reward Networkmentioning
confidence: 99%
“…Elevated c-Fos expression in dmPFC and BLA after OF indicated that modifications may involve the dmPFC-BLA Emotional trauma generates silent synapses W Ito et al pathway. Given the dmPFC-BLA interactions are required for PA learning (Malin et al, 2007;Malin and McGaugh, 2006) and correlate with fear memory (Lesting et al, 2011;Popa et al, 2010), the formation of new silent synapses is a potential mechanism to enhance PA learning via strengthening dmPFC-BLA connectivity.…”
Section: Psychological Trauma and Fear Memorymentioning
confidence: 99%
“…Emotionally salient stimuli generally recruit the dorsomedial prefrontal cortex (dmPFC) and the basolateral amygdala (BLA), which have strong reciprocal projections (Hubner et al, 2014;McDonald, 1998) and are involved in fear learning (Gilmartin et al, 2014;Marek et al, 2013;Senn et al, 2014), including contextual learning during observational fear (Amano et al, 2010;Jeon et al, 2010). Fear learning increases oscillatory synchronization between the two structures (Lesting et al, 2011;Likhtik et al, 2014;Stujenske et al, 2014), the amplitude of which correlates with the strength of fear memory (Popa et al, 2010). On the other hand, synaptic inputs from the medial prefrontal cortex to BLA excitatory neurons become attenuated after fear extinction (Cho et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although recent experiments have shown a role for coherence between the amygdala and prefrontal cortex during rapid eye movement (REM) sleep in fear memory consolidation[25], the role of slow wave sleep (SWS) in memory consolidation has been more intensely studied (for review, see [6]). Network activity during SWS is thought to mediate many of the functions attributed to sleep in memory consolidation[10,26,27,28].…”
Section: Introductionmentioning
confidence: 99%